Electrocardiogram Alterations Associated With Psychotropic Drug Use and CACNA1C Gene Variants in Three Independent Samples. Issue 5 (5th January 2017) - Fabbri, Chiara; Boriani, Giuseppe; Diemberger, Igor; Filippi, Maria Giulia; Ravegnini, Gloria; Hrelia, Patrizia; Minarini, Alessandro; Albani, Diego; Forloni, Gianluigi; Angelini, Sabrina; Serretti, Alessandro
Abstract: Several antipsychotics and antidepressants have been associated with QTc prolongation or other electrocardiogram (ECG) alterations, but their impact is still debated and other risk factors are known to affect QTc. We investigated the effect of antidepressants and antipsychotics on QTc and other ECG intervals/waves in three samples. Two discovery samples (cross‐sectional sample n = 145 and prospective sample n = 68, naturalistic treatment) and a replication prospective sample (Clinical Antipsychotic Trials of Intervention Effectiveness, n = 515, randomized treatment) were analysed. In both prospective samples, baseline/follow‐up changes in ECG parameters were analysed in relation to the number of psychotropic drugs stratified according to their known cardiovascular risk. In the cross‐sectional sample, ECG parameters were compared among drugs with different risk profile. The possible effect of single nucleotide polymorphisms (SNPs) in the CACNA1C gene on QTc was also investigated. There was no evidence of mean QTc prolongation or increased risk of clinically relevant QTc prolongation (≥20 msec.) in association with psychotropic drugs stratified according to their known cardiovascular risk. The prescription of drugs with cardiovascular risk was less common in older individuals or individuals with cardiovascular comorbidities. Other factors (gender, baseline QTc, renal function) affected QTc. rs1006737 and SNPs in linkage disequilibrium with it modulated QTc duration/changes in all samples. An association between risk drugs and shorter RR interval or higher heart rate was found in all samples. A relevant effect of psychotropic drugs with cardiovascular risk on QTc duration was not observed. A number of factors other than psychotropic drugs may influence QTc. CACNA1C rs1006737 may modulate QTc in patients treated with psychotropic drugs.